THE CHALLENGES ASSOCIATED WITH PREDICTING POST-CONCUSSION SYMPTOMS: A SCOPING REVIEW OF LITERATURE - Atayde, Adrienne Lloyd (My University, 2020)
Background: Up to 20% of concussion patients do not recover and develop a host of persisting cognitive, physical, behavioural, and/or emotional symptoms – collectively known as post-concussion syndrome (PCS) – lasting for many months to years. It is unclear why these patients have protracted recovery. Identifying factors that can predict patients at most risk can provide earlier targets for prevention and treatment. However, the wide-ranging list of predictors of PCS is creating confusion in the body of literature, and despite countless reviews attempting to clarify this growing list, there remains a great deal of uncertainty. Objective: To systematically map the reviews on PCS predictors to determine the nature of the reviews and understand why this body of literature still lacks firm, conclusive evidence. We aimed to identify sources of clinical and methodological diversity that hinder meta-analytic syntheses, and in turn, limit the conclusions drawn and translated to clinical practice. Methods: The Joanna Briggs Institute Reviewer’s Manual and the PRISMA-ScR was used to develop our study design. Six databases were searched, including reference lists. Studies needed to sufficiently focus on predicting PCS and report challenges relevant to quantitative synthesis. Results: 281 eligible studies were found. Eleven studies were included in the final qualitative analysis. Qualitative synthesis revealed definitions and diagnostic barriers, as well as methodological barriers, contribute to clinical and methodological diversity in studies. Conclusions: Despite extensive research on PCS predictors, researchers are faced with definitions and diagnostic barriers and methodological barriers that influence the clinical and methodological diversity across studies. These sources of barriers and diversity impede the conduct of more meta-analytic approaches, and in turn, limits review studies from reaching more conclusive evidence that can reliably inform clinical practice. Understanding of the nature of literature reviews can help inform researchers of the sources of diversity and barriers to improve research contributions to evidence-based medicine.